Peran Guru Bimbingan Konseling dalam Mempersiapkan Karir Siswa SMK NU Kajen Pekalongan - El-Muhtadi Rizal, Zacky Al-Ghofir; Khobir, Abdul; Shiva, Aeni; Masykuroh, Siti; Indah Lestari, Nur Khofia (Prodi Bimbingan Konseling FKIP UNDANA, 2025)
Vocational high schools (SMK) play a strategic role in producing graduates who are ready for work. However, students' career readiness is not only determined by technical skills, but also by their ability to plan for the future psychologically and socially. Guidance and Counseling (BK) teachers have an important responsibility in assisting students to recognize their potential, set goals, and make appropriate career decisions. The research question in this study is how BK teachers play a role in preparing students' careers, what obstacles they face, and what strategies they use in providing career guidance services. This study uses a descriptive qualitative approach with data collection techniques through interviews, observations, and documentation of BK teachers at SMK Ma'arif NU Kajen. The purpose of this study is to describe the role of BK teachers, identify the obstacles that arise, and explore the strategies applied in the implementation of career services. The results of the study indicate that the role of guidance counselors includes the functions of facilitator, consultant, and character developer, although it is not yet optimal due to limitations in time, resources, and school policy support. The strategies used include individual approaches, collaboration with the Career Guidance Center (BKK), and strengthening communication with students. Career services require structural support to be more effective and sustainable.